2013
DOI: 10.1113/expphysiol.2012.069096
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular mechanics: important contributors to the increased right ventricular afterload of pulmonary hypertension

Abstract: Chronic hypoxia causes pulmonary vasoconstriction and vascular remodeling, which lead to hypoxic pulmonary hypertension (HPH). HPH is associated with living at high altitudes and is a complication of many lung diseases, including chronic obstructive pulmonary disease, cystic fibrosis, and obstructive sleep apnea. Pulmonary vascular changes that occur with HPH include stiffening and narrowing of the pulmonary arteries that appear to involve all vascular cell types and sub-layers of the arterial wall. Right vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…29,46,47 The Hb index results in PH broilers suggests that individual RBCs had very low Hb content on their membranes, apparently due to increased proportion of immature RBCs in the circulation and enhanced erythropoiesis induced by oxygen deficiency due to cold stress. The findings confirm an accelerated erythropoiesis in PH broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,46,47 The Hb index results in PH broilers suggests that individual RBCs had very low Hb content on their membranes, apparently due to increased proportion of immature RBCs in the circulation and enhanced erythropoiesis induced by oxygen deficiency due to cold stress. The findings confirm an accelerated erythropoiesis in PH broilers.…”
Section: Discussionmentioning
confidence: 99%
“…6,47 This may require further investigation. The increase in the RV/TV ratio with increase in the age of the birds demonstrated that the older the birds, the higher the risk of PH development.…”
mentioning
confidence: 99%
“…Hypoxic pulmonary vasoconstriction (HPV) causes an abrupt change in right ventricular after‐load (Sommer et al . , Wang & Chesler ), but detailed changes of the right ventricle during this acute process have been incompletely documented.…”
mentioning
confidence: 99%
“…3 Furthermore, repetitive hypoxia-induced pulmonary arterial vasoconstriction, occurring during obstructive sleep apneas, may promote remodeling of pulmonary vasculature, resulting in pulmonary artery dilation, with consequent pulmonary hypertension (PH). 4 The study of Dobrowolski et al 5 clearly demonstrates the existing relationship between pulmonary artery dilation and the presence of newly diagnosed severe OSA in patients with resistant hypertension (RHTN). OSA and RHTN are known to have a negative impact on left ventricular morphology and function, 6 while in the present study, the authors 5 established the effects of OSA and RHTN on right ventricular morphology and systolic function and on the parameters associated with pressure in pulmonary circulation.…”
Section: 12mentioning
confidence: 99%
“…4 The study of Dobrowolski et al 5 clearly demonstrates the existing relationship between pulmonary artery dilation and the presence of newly diagnosed severe OSA in patients with resistant hypertension (RHTN). OSA and RHTN are known to have a negative impact on left ventricular morphology and function, 6 while in the present study, the authors 5 established the effects of OSA and RHTN on right ventricular morphology and systolic function and on the parameters associated with pressure in pulmonary circulation.…”
mentioning
confidence: 99%